2004
DOI: 10.1002/jctb.1109
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of citric acid from aqueous solutions with Alamine 336: equilibrium and kinetics

Abstract: Citric acid is one of the organic acids for which the world market is growing every year. This article describes equilibria and kinetic studies for the extraction of citric acid by Alamine 336 with methyliso-butylketone (MIBK) as diluent. The theory of extraction accompanied by a chemical reaction has been used to obtain the intrinsic kinetics of extraction of citric acid by Alamine 336 in MIBK. The reaction has been found to be first order in both Alamine 336 and citric acid with a rate constant of 0.013 m 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Several studies can be found on the reactive extraction of citric acid using the nitrogen-based extractants such as N -substituted alkyl amides, long chain (about 8–12 carbon atoms) alkyl amines, , and so forth. They have reported extraction efficiency as high as 90% using the tertiary amines diluted in active diluents. Studies on the reactive extraction of citric acid related to equilibrium, , kinetics, effects of pH, back extraction, etc., can be found in the literature. Different modeling approaches have also been reported; for example, a mathematical model was obtained by Bizek et al , using the correlation between solvatochromic properties of diluents .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies can be found on the reactive extraction of citric acid using the nitrogen-based extractants such as N -substituted alkyl amides, long chain (about 8–12 carbon atoms) alkyl amines, , and so forth. They have reported extraction efficiency as high as 90% using the tertiary amines diluted in active diluents. Studies on the reactive extraction of citric acid related to equilibrium, , kinetics, effects of pH, back extraction, etc., can be found in the literature. Different modeling approaches have also been reported; for example, a mathematical model was obtained by Bizek et al , using the correlation between solvatochromic properties of diluents .…”
Section: Introductionmentioning
confidence: 99%
“…Both the partitioning coefficient (P) and dimerization constant (D) of MIBK were found to be around 0.152 and 0.795 that resulted in a low distribution coefficient (K D = 0.175). 10 had reported distribution coefficient of 67.147 (E = 98.5 %) using Alamine 336 diluted in MIBK. The extraction efficiency calculated in this work is in good agreement with the literature.…”
Section: Equilibrium Distribution Of Citric Acidmentioning
confidence: 99%
“…The extraction efficiency calculated in this work is in good agreement with the literature. 10,12 The stoichiometry of acid:extractant complex was estimated for chemical extraction of citric acid for all three extraction systems (A336, TBP, and TOA; diluted in MIBK). For TBP and A336, loading ratios (Z) were obtained to be low (Z<0.5), thus, only (1:1) acid:extractant complex formation was assumed.…”
Section: Equilibrium Distribution Of Citric Acidmentioning
confidence: 99%
See 2 more Smart Citations